Pedagogical And Psychological Mechanisms For Enhancing The Effectiveness Of Teachers’ Professional Activity Based On Metacognitive Factors - Raximov Zoyir Jumayevich (International Journal on Integrated Education, 2026)
This study explores the pedagogical and psychological mechanisms for enhancing the effectiveness of teachers’ professional activity based on metacognitive factors. Metacognition, understood as awareness and regulation of one’s own thinking processes, plays a crucial role in improving instructional quality, reflective practice, and professional growth. The research analyzes how metacognitive skills—such as self-monitoring, self-assessment, planning, and self-regulation—contribute to teachers’ decision-making, classroom management, and instructional strategies. Special attention is given to reflective practice, emotional regulation, motivation, and professional self-awareness as psychological mechanisms that strengthen pedagogical performance. The study emphasizes that integrating metacognitive training into professional development programs fosters adaptive expertise, critical thinking, and continuous improvement. Furthermore, the paper identifies practical strategies for implementing metacognitive approaches in teacher education, including reflective journals, peer feedback, and formative assessment techniques. The findings suggest that systematic development of metacognitive competence enhances teaching effectiveness, student engagement, and overall educational quality.